Managerial Objectives in Regulated Industries: Expense-Preference Behavior in Banking - Edwards, Franklin R. (Journal of Political Economy, 1977)
Recent work on the theory of the firm under regulation suggests that managers of regulated firms may be utility maximizers rather than profit maximizers. There is, however, very little empirical evidence on managerial behavior in regulated industries. This article examines one kind of utility-maximizing behavior that seems particularly applicable to regulated firms: expense-preference behavior. Specifically, I develop a test capable of discriminating between expense-preference and profit-maximizing behavior and apply it to the banking industry, a highly regulated industry. My findings indicate that an expense-preference theoretical framework better explains the behavior of regulated firms than does a profit-maximization framework.